Summer Fling - Tredoux, Caitlin (Department of English Language and Literature, 2015)
Two estranged sisters, Liza and Nikki, travel to the seaside town of Hermanus. Liza hopes that a summer spent together will restore their once close relationship. Nikki is just looking for some fun. Then Liza disappears from the family holiday house. Messages left show that she's been abducted, kidnapped by someone who has no idea that Liza desperately needs her medication. In a country plagued by violence against women, Nikki, her parents, and the local police need to work together against the clock to save Liza. If only they could trust each other. Nikki is drawn deeper into a situation she cannot control or run away from as she tries to find her sister before it’s too late. Toxic family history emerges and tensions mount as the kidnappers demand a large ransom. Liza’s health is deteriorating fast and Nikki’s efforts to make amends are met with doubt and hostility. Will Nikki be able to help her sister before it’s too late?